Simulation Studies on Fluid Catalytic Cracking Riser Reactor - Arya, Divyanshu (My University, 2013)
The fluid catalytic cracking unit(FCC) is of great importance in petroleum refining industry as it treats heavy fractions from various process units to produce light ends (valuable products). The main units of FCC are riser, catalyst stripper and regenerator. Riser reactor is the most important part of this unit as the cracking reactions take place in the riser. Modeling and simulation of riser helps in understanding the complex physical phenomena taking place in FCC riser unit. Modeling difficulties in FCC riser unit includes complex hydrodynamics, unknown hydrocarbons in the FCC feed and involvement of different type of simultaneous reactions. There has been lot of progress in the modeling of riser reactor. Most of the researchers have taken four to five lump model to avoid complexities in determining reaction rates. These models are easy to integrate with the material and energy balance equations. In the literature two phase hydrodynamics models are used by many authors, heat and mass transfer resistances are ignored in many studies and exponential catalyst deactivation model is used in most works. In this work, FCC riser is simulated solving the material and energy balance equations considering four lump reaction kinetics, deactivation based on coke concentration on catalyst, 2 phase hydrodynamics and interphase mass transfer phenomena. A computer program is developed in C for the model solution. A base case model for the FCC riser is solved assuming constant cluster size of 6mm.Various cluster size correlations are used in base model to predict the product yields. The predicted cluster size varies considerably for different correlations. The results show significant variation in conversion, gasoline, and coke for these correlations. The correlations that predict larger cluster predict low overall conversion as compared to the correlations that predict smaller size clusters. Coke yield prediction is most influenced by the cluster size.
M.Tech.
Keywords: Fluid Catalytic Cracking, riser reactor; Simulation